MCSE NT Server 4.0 study guide : (Osborne McGraw-Hill, 1998)
Proven classroom techniques: the only study guides to be based on the world's most successful and sought after exam preparation curriculum; approved and authorized by Microsoft's stringent ICV program; unique in detail and focus: presents only solutions that are acceptable on MCSE exams--no red-herrings or alternate, but unauthorized, ``options''; ``from the Class Room'' and ``EXAM WATCH'' sidebars--plus special Test-taking Techniques chapter--focus students on their goal: preparing and passing the exam; the first study guides to include Microsoft's new SIMULATION QUESTIONS on CD--soon to be included in every MCSE exam; paractice makes perfect! Contains over 1000 questions--more sample tests than any other available study guide--including 6 exams on CD; stuck on an exam question? The answer is just a click away with the electronically cross-referenced Study Guide on CD. You can even add marginal notes and book mark the CD for easy reference; CD includes internet links to valuable certification-focused web sites and multimedia computer-based-training modules for re-enforcement and skill building, plus special membership on GKN's web-based training site containing up-to-the-minute certification information.